The on-site quality-assurance system for Hyper Suprime-Cam: OSQAH†. (22nd September 2017) - Furusawa, Hisanori; Koike, Michitaro; Takata, Tadafumi; Okura, Yuki; Miyatake, Hironao; Lupton, Robert H; Bickerton, Steven; Price, Paul A; Bosch, James; Yasuda, Naoki; Mineo, Sogo; Yamada, Yoshihiko; et al.
Abstract: We have developed an automated quick data analysis system for data quality assurance (QA) for Hyper Suprime-Cam (HSC). The system was commissioned in 2012–2014, and has been offered for general observations, including the HSC Subaru Strategic Program, since 2014 March. The system provides observers with data quality information, such as seeing, sky background level, and sky transparency, based on quick analysis as data are acquired. Quick-look images and validation of image focus are also provided through an interactive web application. The system is responsible for the automatic extraction of QA information from acquired raw data into a database, to assist with observation planning, assess progress of all observing programs, and monitor long-term efficiency variations of the instrument and telescope. Enhancements of the system are being planned to facilitate final data analysis, to improve the HSC archive, and to provide legacy products for astronomical communities.